Consensus Statement on the Management of Duchenne Muscular Dystrophy in Saudi Arabia During the Coronavirus Disease 2019 Pandemic - Bamaga, Ahmed K.; Alghamdi, Fouad; Alshaikh, Nahla; Altwaijri, Waleed; Bashiri, Fahad A.; Hundallah, Khalid; Abukhaled, Musaad; Muthaffar, Osama Y.; Al-Mehmadi, Sameer; Jamaly, Tahani Ahmed; Al-Muhaizea, Mohammad A.; Al-Saman, Abdulaziz (Frontiers in Pediatrics, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has caused overwhelming challenges in healthcare worldwide. During such an outbreak, some needs of high-risk groups who require regular follow-ups and long-term management are not met. The vulnerable populations include patients with Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD). DMD is characterized by respiratory complications caused by muscle weakness. Hence, patients with this condition are at high risk of severe diseases including COVID-19. Methods: To standardize care and provide optimal treatment to DMD/BMD patients in Saudi Arabia during the COVID-19 pandemic, a panel of experts including neurologists and pediatricians consolidated recommendations for healthcare professionals and caregivers. Results: During this pandemic, substituting unnecessary clinic visits with virtual clinic services was highly recommended, if possible, without compromising clinical outcomes. DMD patients with respiratory complications should be closely monitored, and those with cardiovascular complications must continue taking angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. Moreover, individualized home-based rehabilitation management was preferred. Glucocorticoid and new gene correction therapies should be continued. However, new gene correction therapy must be postponed in newly diagnosed patients. A multidisciplinary decision was required before the initiation of hydroxychloroquine based on the COVID-19 treatment protocol. Conclusion: COVID-19 has caused challenges and transformed access to health care. However, these limitations have provided opportunities for the health care system to adapt. Further, telemedicine has become a reliable platform for follow-up appointments that should be conducted by a multidisciplinary team including physicians, dieticians, and physical therapists.